2016
DOI: 10.1182/blood-2016-02-695312
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of acute myelogenous leukemia stem cell properties after treatment and progression

Abstract: • Using AML as a model, we investigated the effect of treatment and disease evolution on functionally defined cancer stem cell populations.• We demonstrate large-scale changes in LSC frequency and phenotype after relapse, best described using highdimensional space analyses.Most cancers evolve over time as patients initially responsive to therapy acquire resistance to the same drugs at relapse. Cancer stem cells have been postulated to represent a therapy-refractory reservoir for relapse, but formal proof of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
181
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(185 citation statements)
references
References 34 publications
(32 reference statements)
3
181
0
1
Order By: Relevance
“…Thus, studies have shown that LSCs can be found in subpopulations other than the CD34+/CD38-cells and that these LSC containing subpopulations have rapidly cycling cells. 52 It could also be shown that the LSC frequency can vary by almost three orders of magnitude between different leukemias, ranging from 1 in 10 000 to less than 1 in 5 million. 27,30 LSC frequencies in human AML can only be measured using limiting dilution assays in immunodeficient mice (see above for the limitations of these assays).…”
Section: Lscs In Human Myeloid Leukemiamentioning
confidence: 96%
“…Thus, studies have shown that LSCs can be found in subpopulations other than the CD34+/CD38-cells and that these LSC containing subpopulations have rapidly cycling cells. 52 It could also be shown that the LSC frequency can vary by almost three orders of magnitude between different leukemias, ranging from 1 in 10 000 to less than 1 in 5 million. 27,30 LSC frequencies in human AML can only be measured using limiting dilution assays in immunodeficient mice (see above for the limitations of these assays).…”
Section: Lscs In Human Myeloid Leukemiamentioning
confidence: 96%
“…Recently it was shown that the constitution of AML at relapse may differ from diagnosis due to clonal changes including clonal evolution, clonal regression and clonal selection, with possible changes on immunophenotypic [32,33], cytogenetic [34], genetic [34,35] and epigenetic [35] level. Detailed whole genome sequencing studies, analyzing paired diagnosis-relapse samples, showed that at time of diagnosis, patients could present with a wide array of small subclones of which some remained in relapse [36]: indicative for clonal selection under therapy pressure.…”
Section: Lsc Heterogeneity Of Lsc Within a Patientmentioning
confidence: 99%
“…7, 8, 9, 10, 11, 12 Despite this great leap forward in the understanding of the cellular biology of the disease 20 years ago, culture methods able to maintain LSC activity of human primary samples in vitro were only developed recently, eventually enabling relevant cell-based interrogation of the disease. 13 …”
Section: Introductionmentioning
confidence: 99%